Arthropod symbioses: a neglected parameter in pest- and disease-control programmes - Zindel, Renate; Gottlieb, Y.; Aebi, Alexandre (My University, 2011)
1. Arthropods are important players in biological control as pests, control agents and transmitters of invertebrate diseases. Arthropods are frequently infected with one or several micro-organisms, serving as micro-ecosystems in which multiple interactions can take place. These micro-organisms include disease agents and symbiotic micro-organisms. The latter are usually vertically transmitted and can have a broad spectrum of effects on their hosts, ranging from reproductive manipulations to protection against natural enemies. These interactions may directly or indirectly alter the biology of many arthropods in agriculturally, medically and ecologically relevant ecosystems. 2. Symbiotic micro-organism-induced reproductive manipulations such as cytoplasmic incompatibility and parthenogenesis induction can substantially affect the rearing of biological control agents. Many insects, and recently also mites and nematodes, have been found to be infected, displaying a wide range of effects. We discuss examples of arthropod-micro-organism interactions and effects, which could have consequences for the practical application of arthropods in biological control. 3. Symbiotic micro-organisms can also be involved in host protection against natural enemies such as parasitoids, pathogenic bacteria, fungi and viruses. 4. Symbiotic bacteria can influence the vectorial capacity of disease-vectoring arthropods and may be very helpful in decreasing the transmission of disease agents. 5. Synthesis and applications. The effect of micro-organisms on the outcome of biological control programmes is usually not considered in risk assessments and failure analyses. This review emphasizes the importance of endosymbiotic micro-organisms in comprehensive biological control programmes and provides recommendations on how to recognize, avoid or benefit from these influential tenants.